The invention of heritage in the Mediterranean. Images and uses of cultural heritage in the Mediterranean - Isnart, Cyril (2012)
Since it has always been a region of movement and inter-action between peoples, the Mediterranean is seen by the social sciences as a vast arena, full of contrasts. It is a region strongly marked by history – a history shared by the many cultures which have always intermingled, crossed paths – and sometimes swords – here. While some of its peoples are the result of peaceful inter-breeding and others the fruit of a political will to expand and dominate, all the populations bordering the Mediterranean can claim religious or cultural distinctiveness. By maintaining specific identities, such as laying claim to a certain group of symbols, they rely on the legacy of the great civilizations of the past which flourished on their territories. From the earliest times the region had been criss-crossed by people, but this way of seeing Mediterranean cultures came largely from a discovery of a Mediterranean by men of learning – archaeologists, travellers and the military – who described, drew and studied what they found. From the invention of the Mediterranean as a place of monuments to the current management of heritage resources, the way the Mediterranean heritage is used offers a good perspective from which to question the ways certain images of the Mediterranean are re-enforced and how the ideology at the root of heritage preservation is put into practice in this very specific space.